2016
DOI: 10.1016/j.antiviral.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody to ameliorate central nervous system infection and improve survival in a murine model of human Enterovirus-A71 encephalomyelitis

Abstract: Keywords:Enterovirus A71 Monoclonal antibody Therapeutic used Mouse model of human EV-A71 encephalomyelitis a b s t r a c t Background: Enterovirus A71 (EV-A71) encephalomyelitis is an often fatal disease for which there is no specific treatment available. Passive immunization with a specific monoclonal antibody to EV-A71 was used on a murine model of EV-A71 encephalomyelitis to evaluate its therapeutic effectiveness before and after established central nervous system (CNS) infection. Methods: Mice were intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Briefly, the serum samples were serially diluted up to 1:512 and mixed equally with 100 CCID 50 of EV-A71. 28 The samples were then incubated at 4 °C overnight before inoculation onto Vero cell monolayers in 96-well plates; the samples were cultured for seven days at 36 °C. Monoclonal mouse anti-EV-A71 antibody was used as a positive control, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the serum samples were serially diluted up to 1:512 and mixed equally with 100 CCID 50 of EV-A71. 28 The samples were then incubated at 4 °C overnight before inoculation onto Vero cell monolayers in 96-well plates; the samples were cultured for seven days at 36 °C. Monoclonal mouse anti-EV-A71 antibody was used as a positive control, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…BB1A5 recognized a linear epitope spanning amino acids 136–155 in the VP2, and passive transfer of BB1A5 was able to provide 100% protection for the new-born mice challenged with a mouse-adapted EV-A71 strain. Besides that, another group identified a mAb designated as 3D1 belonging to the IgM isotype generated by immunizing mice with a mouse-adapted EV-A71 strain [68]. They demonstrated that passive immunization using 3D1 prevented central nervous system (CNS) infection.…”
Section: Neutralizing Antibodies Against Hfmd Etiological Agentsmentioning
confidence: 99%